Educação e opressão de gênero na obra “Mitos da dominação masculina”: um estudo fundamentado na ontologia marxiana - Lima, Ana Joza de (2021)
The study deals with the relationship between education and gender oppression, aiming to understand the role of the educational complex in the reproduction of this social problem. To achieve this goal, we analyzed the work "Myths of Male Dominance", written by Eleanor Burke Leacock (2019), in order to understand the role of education in the process of transition from a society based on egalitarianism to new relationships based on exploitation and in gender oppression; we also examined the historical and socio-cultural foundations of gender oppression from the point of view of Marxist contributions, as well as we analyzed the ontological nature of education, pointing out its role in the reproduction of exploitative and oppressive relations within class society, along with their limits and contradictions regarding gender oppression. The theoretical-methodological assumption of our research is the ontology of social being founded by Karl Marx (1818-1883), through which we sought to apprehend the nature and specificity of gender oppression and the educational complex as historical and socio-cultural processes based on the way human beings produce their existence in the context of social reproduction. The exposition of the research is displayed in 4 (four) chapters, the first being dedicated to the analysis of the ethno-historical data presented in the work "Myths of male dominance ", the second, to the study of the historical foundations of gender oppression, the third treating about the ontological nature of education from the perspective of the Marxian-Lukacsian contributions. In the fourth and last chapter, we discussed the relationship between education and gender oppression, resuming the experience of peoples narrated in the work of Leacock (2019) and including new elements that show the oppressive character of educational practices carried out in that society, in addition to broadening this debate in view ofthe considerations about how school education has historically contributed to the social reproduction of gender oppression. The discussions carried out reinforce the pressing need for greater clarification about the socio-cultural and historical bases of gender inequalities and the place of education in the social reproduction of these relationships, revealing their contradictions and limits. Based upon the experience of the MontagnaisNaskapi, we emphasized that education, when put to meet the interests of class society, became an oppressive practice insofar as it had the primary function of accelerating and consolidating the changes that had been taking place on the framework of the social structure; corroborating the process of transition from egalitarian social relations to relations of exploitation and gender oppression.